Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1002/cbic.201500641
|View full text |Cite
|
Sign up to set email alerts
|

TP‐2Rho Is a Sensitive Solvatochromic Red‐Shifted Probe for Monitoring the Interactions between CDK4 and Cyclin D

Abstract: Understanding the intricate steps of protein kinase regulation requires characterization of protein-protein interactions between the catalytic subunit, its regulatory partners and the substrate. Fluorescent probes are useful tools with which to study such interactions and to gain insight into their affinities and specificities. Solvatochromic probes, which display changes in their fluorescence emission in response to changes in the polarity of the medium, are particularly attractive. Here we describe conjugati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…To this aim, we first asked whether other fluorescent probes than FITC might enable a greater response to R248Q, relative to WT p53 (Figure A). Results revealed TP2Rho, a highly sensitive water‐soluble solvatochromic vinyltriphenylamine dye, which we previously used to probe peptide and protein interactions in vitro, as the best candidate. We therefore prepared the p254C‐TP2Rho conjugate (Scheme ), for incubation with recombinant GST‐tagged p53 expressed in Escherichia coli , purified by means of fast protein liquid chromatography (FPLC) and subjected to thermo‐denaturation at different temperatures for 15 min.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To this aim, we first asked whether other fluorescent probes than FITC might enable a greater response to R248Q, relative to WT p53 (Figure A). Results revealed TP2Rho, a highly sensitive water‐soluble solvatochromic vinyltriphenylamine dye, which we previously used to probe peptide and protein interactions in vitro, as the best candidate. We therefore prepared the p254C‐TP2Rho conjugate (Scheme ), for incubation with recombinant GST‐tagged p53 expressed in Escherichia coli , purified by means of fast protein liquid chromatography (FPLC) and subjected to thermo‐denaturation at different temperatures for 15 min.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we reported on the design and characterisation of a fluorescent peptide biosensor derived from the main aggregation‐nucleating motif of p53, for detection of the R248Q mutant. This biosensor was engineered through conjugation of a highly sensitive solvatochromic dye, TP2Rho, that we previously implemented to monitor protein–protein and protein–peptide interactions in vitro . We have shown that this biosensor interacts with the self‐aggregation motif of p53 itself in vitro and that it preferentially interacts with recombinant R248Q mutant over WT p53.…”
Section: Resultsmentioning
confidence: 99%
“…[31,34] The rhodanine benzylidene conjugates also resemble the structure of the GFP chromophore and as imilars caffold can be found, fori nstance,o np reviouslyr eported protein or RNA aptamersf luorogens, which makesi to verall promising for our purposes. [35][36][37] The probes were obtainedt hrough as traightforward synthesis, using the Knoevenagel condensation of rhodanine-3-acetic acido nt he corresponding startinga ldehydes, followed by an amide coupling with ah alogenoalkane chain (Scheme S1).…”
Section: Probe Designmentioning
confidence: 99%
“…Some similar frameworks to the structure of the rhodanine benzylidene conjugates have also been previously reported as protein or RNA aptamer fluorogens, which encourage us to select this probe for our present investigation. 63,64 To achieve our goal, the probe HJRA was synthesized by a simple condensation reaction between compound 1 and rhodanine-3acetic acid in ethanol (Scheme 1) and well characterized by 1 H NMR (Figure S4), 13 C NMR (Figure S5), HRMS (Figure S6), and IR (Figure S7) spectroscopies.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%